Morphological processing across the adult lifespan: a tale of gains and losses - Reifegerste, Jana (Journal of Language and Aging Research, 2024)
Despite increasing research on language in aging, age effects on morphological processing have received comparatively little attention. Some previous evidence suggests that while regular morphology (e.g., walk-walked) may remain relatively stable in older age, irregular morphology (e.g., bring-brought) shows signs of age-related decreases in processing efficiency. However, the underlying reasons for these declines are unclear. The current study sought to investigate the cognitive underpinnings of age-related effects on German noun plurals: default plurals (posited to follow a default rule [e.g., Zebra-Zebras 'zebra(s)']) and predictable and unpredictable non-default plurals (closed class plurals, in which the plural is either phonologically predictable from the singular [e.g., Flasche-Flaschen 'bottle(s)'] or unpredictable [e.g., Nest-Nester 'nest(s)']). In a cross-modal priming experiment, 283 healthy German native speakers (aged 18–91 years) performed lexical decisions on singular nouns which take different types of plural affixes, and which were primed by either their plural form ("morphological condition") or an unrelated noun ("unrelated condition"). Additionally, several cognitive abilities (declarative, procedural, and working memory, interference control, processing speed) were tested to assess their mediating role for morphological processing. The results revealed distinct developmental trajectories for default versus non-default plurals: priming effects (unrelated-morphological condition) for predictable and unpredictable non-default plurals decreased with increasing age, with age-related declines in declarative memory mediating these declines. In contrast, priming effects for default plurals increased with increasing age. Although the reasons for this increase remain to be clarified, we suggest lifelong experience with the computation of these forms as a possible mechanism.